RhoB regulates prostate cancer cell proliferation and docetaxel sensitivity via the PI3K-AKT signaling pathway - Tiantian Sheng; Hang Su; Lu Yao; Zhen Qu; Hui Liu; Wenjuan Shao; Xiangyu Zhang (BMC Cancer)
Abstract Docetaxel is a widely used first-line treatment for castration-resistant prostate cancer (CRPC). RhoB, a member of the Rho GTPase family, plays a major role in prostate cancer metastasis by modulating the PI3K-AKT signaling pathway. It is crucial in regulating cytoskeletal reassembly, cell migration, focal adhesion (FA) dynamics. To investigate RhoB’s function in prostate cancer, CRISPR/Cas9 gene editing technique was utilized to knock out the RhoB gene in prostate cancer cells. Successful gene editing was confirmed by using T7 endonuclease I (T7EI) assays and Sanger sequencing. Knocking out RhoB enhanced epithelial–mesenchymal transition (EMT) and decreased the IC50 value of docetaxel in RhoB-knockout PC-3 cells. This suggests increased sensitivity to docetaxel. Furthermore, RhoB knockout prompted the migration and invasion of prostate cancer cells, effects that were reversed upon RhoB overexpression. Interestingly, RhoB status did not significantly influence the cell cycle of prostate cancer cells. RNA sequencing of PC-3 cells with either overexpressed or knock-out RhoB revealed that RhoB regulates pathways involved in FA, ECM receptor interaction, and PI3K-AKT signaling. These pathways directly influence the EMT process, cell migration, and invasion in prostate cancer cells. Notably, RhoB overexpression activated PI3K-AKT signaling when PC-3 cells were treated with low concentration of DTXL (50 nM, 72 h). This activation reduced DTXL’s cytotoxicity, suggesting may confer chemoresistance via PI3K-AKT pathway activation.